The antiepileptic effect of Gastrodiae Rhizoma through modulating overexpression of mTOR and attenuating astrogliosis in pilocarpine mice model. Issue 1 (13th December 2019) - Yip, Ka Lai; Koon, Chi Man; Chen, Zi Yi; Chook, Ping; Leung, Ping Chung; Schachter, Steven; Leung, Wai Hong; Mok, Chung Tong; Leung, Howan
Abstract: Objective: To investigate the effect of water extract of Gastrodiae Rhizoma (GR) on the development of acquired temporal lobe epilepsy (TLE) and on regulating the expression of the mammalian target of rapamycin (mTOR) and semaphorin 3F (SEMA3F). Methods: A pilocarpine‐induced status epilepticus (SE) model was adopted to precipitate injury in the limbic systems. GR and carbamazepine (CBZ) treatments were given to mice for 14 days prior to SE induction to demonstrate the antiepileptic effects and continued for 5 more days to illustrate the effects on histologic studies. Results: Our results consolidated that GR treatment (92.1 minutes) could delay the SE onset in comparison with the control group (61.5 minutes, P = .041). Fewer mice had reached SE with GR treatment (41.7%) when compared with the control group (83.3%, P = .044). GR treatment (2.1 hours/mouse) could suppress the number of acute seizures in post‐SE survival mice when compared with the control group (4.5 hours/mouse, P < .001). The effects of GR treatment were elucidated with the mechanism of actions. GR treatment reduced the overexpression of mTOR (0.27 vs 0.67 AU/mg protein, P = .047). GR treatment increased the underexpression of SEMA3F (0.51 vs 0.16 µg/mg protein, P = .034). In the histochemical study of microtubule‐associated protein 2 (MAP2) staining, our results showed that GR prevented neuronal loss in the GR treatment group (64.8% positively stained pixel area) as compared with the control group (59%, P = .014) in the hippocampus. In glial fibrillary acidic protein (GFAP) staining, the severity of astrogliosis was mitigated by the GR treatment (4.1% positively stained pixel area) when compared to the control group (5.6%, P = .047) in the hippocampus. Significance: These results provide preclinical evidence to support the use of GR, which could suppress acute seizures and relieve pathological changes in pilocarpine‐induced TLE mice. We demonstrated that the antiepileptic effects of GR could be accompanied by mTOR reduction and astrogliosis attenuation.